Day 3 neutrophil-to-lymphocyte ratio and its derived indices predict 90-day poor outcomes following mechanical thrombectomy in acute ischemic stroke patients - Gao, Weiwei; Annadurdyyev, Arslan; Yu, Lingfeng; Huang, Rong; Liu, Bin; Lin, Yixiong; Li, Huaiyi; Zhu, Renjing (Frontiers in Neurology, 2024)
ObjectiveTo investigate the dynamic changes in neutrophil–to–lymphocyte ratio (NLR) and its derived indices following mechanical thrombectomy (MT) in patients with acute ischemic stroke (AIS) and evaluate their predictive value for prognosis.MethodsThis single-center retrospective cohort study included AIS patients who underwent MT at Zhongshan Hospital of Xiamen University from January 2018 to February 2024. Peripheral blood samples were collected on admission, day 1, and day 3 after MT to determine the NLR, derived NLR (dNLR), and neutrophil–monocyte–to–lymphocyte ratio (NMLR). The primary endpoint was poor functional outcome at 90 days (modified Rankin scale score 3–6). The secondary endpoints included post-operative hemorrhagic transformation, malignant cerebral edema, in-hospital mortality, and 90-day all-cause mortality. Receiver operating characteristic (ROC) curve analysis was used to evaluate predictive performance, and multivariate logistic regression models were employed to explore the independent associations between inflammatory markers and prognosis.ResultsA total of 423 eligible patients were included. Both groups showed similar dynamic trends in inflammatory markers, peaking on day 1 post-MT and subsequently declining. However, the poor outcome group (n = 255, 60.28%) maintained higher levels on day 3, whereas the good outcome group showed a significant decreasing trend. ROC curve analysis revealed that the NLR (AUC = 0.85, 95% CI: 0.81–0.89), dNLR (AUC = 0.86, 95% CI: 0.82–0.89), and NMLR (AUC = 0.85, 95% CI: 0.81–0.89) on day 3 post-MT had the strongest predictive power for 90-day poor outcomes. After comprehensive adjustment for confounders, these inflammatory markers were independently associated with 90-day poor outcomes: for each unit increase in the NLR, the risk of poor outcome increased by 38% (OR = 1.38, 95% CI: 1.28–1.49, p < 0.001); for dNLR, it increased by 104% (OR = 2.04, 95% CI: 1.73–2.40, p < 0.001); and for NMLR, it increased by 35% (OR = 1.35, 95% CI: 1.26–1.45, p < 0.001).ConclusionInflammatory markers (NLR, dNLR, and NMLR) on day 3 post-MT can serve as independent predictors of prognosis in AIS patients treated with MT. Dynamic monitoring of inflammatory markers may facilitate early risk stratification and guide individualized treatment strategies.